Optimasi Penggunaan Whatsapp Business Sebagai Sarana Pengembangan Pemasaran Usaha Pada Masyarakat Tanggamus Sumber Mulyo - Rahyono, Rahyono; Nursari, Ayu; Pratama, Reza Hardian; Khotimah, Ayyumi Khusnul (University of Muhammadiyah Sumatera Utara, 2024)
To improve the local economy in Sumber Mulyo village, use WhatsApp business as a business marketing tool, to expand information and increase opinions for the Sumber Mulyo community. This community service activity aims to increase knowledge and insight regarding digital marketing, especially focusing on using WhatsApp. business to be more optimal in marketing products so that product sales increase and increase family income. This activity was attended by the Sumber Mulyo community who already have or already have a WhatsApp account, but others have not used WhatsApp which is specifically used for business, namely WhatsApp Business. Training is carried out using each member's device so that it can be directly applied to their respective businesses and products during training. The results of this training are very enthusiastic about optimizing the use of WhatsApp Business as a product marketing medium, however this training still requires advanced training in the aspect of creating WhatsApp story content to make it more attractive to potential buyers.